An Analysis of TOEIC Scores of State Bengkalis Politechnic Students in Institutional TOEIC Training - Ari Satria (ELT-Lectura, 2020)
In improving students' English competence, Bengkalis State Polytechnic holds TOEIC Institutional training for students who have obtained TOEIC scores above 400 for diploma three and 450 for diploma four. Students must have a good English certificate in order to continue their studies, scholarships and apply for work. This study was conducted to determine whether there are differences in TOEIC scores in Institutional TOEIC Training for students between classes A, B and C. Data analysis was done by Anova using SPSS version 22. The population in this study was 60 students. The results of this study indicate that student learning outcomes or TOEIC scores in the Institutional TOEIC Training between class A, class B and class C are significantly different.